Effect of beta-lactams on peptidoglycan metabolism of Haemophilus influenzae grown in animals. - Rousseau, N (1992)
We have examined bacterial determinants that influence beta-lactam activity in Haemophilus influenzae cells cultivated in a system that reproduces in vivo growth conditions. Bacteria grown in diffusion chambers were recovered from the peritoneal cavities of rats, and their cell properties were compared with those of bacteria grown in broth cultures by various tests performed in vitro. The rate of peptidoglycan synthesis was measured as the incorporation of [14C]alanine into cell wall material in the presence of chloramphenicol. The total incorporation of [14C]alanine into peptidoglycan was markedly increased in cells grown in rats prior to the assay but was efficiently reduced by the beta-lactams. The extent of cross-linking was lower in the peptidoglycan of in vivo-grown bacteria, as estimated by sodium dodecyl sulfate- to trichloroacetic acid-insoluble radioactive cell wall material ratios. A whole-cell labeling assay with 125I-penicillin was used to characterize the penicillin-binding proteins (PBPs). Four PBPs showed a striking reduction in the binding of the labeled penicillin in cells grown in rats. Such changes resembled the PBP alterations seen in beta-lactamase-negative clinical strains that were resistant to the beta-lactams. Although ampicillin and moxalactam showed delayed inhibitory activities in vitro for cells collected from rats, cells recovered from beta-lactam-treated rats showed evidence of antibiotic effectiveness (binding of the beta-lactams to PBPs in vivo and altered morphology), and the killing of cells exposed to antibiotics in broth or in peritoneal fluid was equally good. Finally, the frequencies of spontaneous resistance or tolerance to ampicillin or moxalactam were estimated, and there was no significant difference for in vitro- or in vivo-grown cells. These data demonstrated that the cultivation of H. influenzae in animals created changes in PBPs and the overall peptidoglycan metabolism. Such alterations did not impair the bactericidal activities of the beta-lactams, although they resulted in delayed bacterial inhibition, a phenomenon that may have important consequences in antibiotherapy.